Analisis Biaya Sumberdaya dalam Negeri dan Kepekaannya pada Usaha Ternak Babi di Sumatera Utara - Budiman Hutabarat; Bambang Winarso (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1994)
North Sumatera has exercised its comparative advantage in various forms of farm activities including pig raising undertaking. The paper aims to analyze the domestic resource costs and its sensitivity in pig farming in the province. Empirical data were obtained from six pig farming enterprises and eleven